Gender Differences in Pain Intensity and Functional Performance among Older Adults with Knee Pain living in Suburban of Bangkok, Thailand - Pattaraporn Piwong; Tiwaporn Junkhaw; Ratana Somrongthong (Indian Journal of Forensic Medicine & Toxicology, 2022)
Purpose of study: To investigate gender-related differences in pain intensity functional performance among olderadults with knee pain who live in the suburban area of Bangkok, Thailand.Method: This cross-sectional study recruited 220 older adults who suffering from knee pain, aged between50-65 years(male=79, female =141). A convenience sampling method was used to select the participants in thisstudy, each participant underwent an actual functional performance test such as TUG, 30CST, and completedself-report questionnaires consist of demographic characteristics, NPRS, and KOSADLS. An independent samplest-test was used as appropriate to determine gender differences.Results: Males and females had a difference in two aspects, females have significantly more pain intensity(NPRSscores of female:4.88 ±1.20; male: 3.99 ±1.27, p < 0.001), and poorer functional performance also more impairmenton a specific functional task such as KOSADLS scores (female:71.74 ±7.49; male:74.67 ±5.01,p< 0.01), TUGscores(female:11.66 ±1.11; male:10.81 ±1.06, p< 0.001) and 30CST scores (females:11.23 ±1.40; male:12.50 ±1.44,p < 0.001).Conclusion: The differences between genders regarding pain intensity and functional performance which areassessed by self-report measure and actual functional performance test, these two methods provide valuableinformation. The difference evaluation and preventive health care strategies based on gender differences wouldbe considered in Thai older adults with knee pain to improve their knee function and reduce the pain.